Diurnal Release of Airborne Pathogen Spores in Greenhouses via the Synergistic Effects of Relative Humidity and Wind - Jiayi Ma; Ali Chai; Yanxia Shi; Xuewen Xie; Lei Li; Sheng Xiang; Xianhua Sun; Tengfei Fan; Baoju Li (Advanced Science)
Abstract The occurrence of diseases during greenhouse vegetable cultivation is becoming increasingly severe. Humidity and wind are important factors affecting the spread of many pathogenic fungal spores, but it remains difficult to explain the phenomenon of rapid spore spread in greenhouses. Here, the detachment of spores from hyphae during rapid drops in humidity and their subsequent dispersal due to wind is detailed. It is demonstrated that Corynespora cassiicola spores exhibit jerking movements during humidity reduction, resulting in spore discharge, and that spore connections are weaker in high‐humidity environments than in low‐humidity environments. This investigation across the fungal kingdom further reveals that jerking movements are common in the tested hyphomycete spore species. Spores rely mainly on wind to spread after being discharged from hyphae, and their spread range is influenced by factors such as wind speed, spore source height, and spore age. In summary, it is discovered that the combined effects of diurnal humidity fluctuations and wind drive the rapid spread of pathogenic spores in greenhouses, providing a theoretical basis for optimizing control strategies for airborne fungal diseases in greenhouses.